Complete the process of solving the equation.

Fill in the missing term on each line. Simplify any fractions.
20(c–11)= –20

c–11=
Divide both sides by 20
c=
Add 11 to both sides

1 answer

Let's complete the process of solving the equation step by step, filling in the missing terms.

  1. Start with the given equation: \[ 20(c - 11) = -20 \]

  2. Divide both sides by 20: \[ c - 11 = \frac{-20}{20} \] This simplifies to: \[ c - 11 = -1 \]

  3. Now add 11 to both sides: \[ c = -1 + 11 \] Simplifying this gives: \[ c = 10 \]

So, the completed process looks like this:

  1. \( c - 11 = -1 \)
  2. \( c = 10 \)
Similar Questions
  1. Complete the process of solving the equation.Fill in the missing term on each line. Simplify any fractions. 2(c + 6) = 12 c + 6
    1. answers icon 1 answer
  2. Complete the process of solving the equation.Fill in the missing term on each line. Simplify any fractions. 2(u+5)=10 u+5=
    1. answers icon 1 answer
  3. orComplete the process of solving the equation. Fill in the missing term on each line. Simplify any fractions. – 2(15r–12)=
    1. answers icon 1 answer
  4. Complete the process of solving the equation.Fill in the missing term on each line. Simplify any fractions. c/ –5–10=5 c/
    1. answers icon 1 answer
more similar questions